Exemplary Language Practice in Maharah Kalam Learning: Praktik Bahasa yang Teladan dalam Pembelajaran Maharah Kalam - Zahro, Nurin Nadhifatus; Fauji, Imam (Indonesian Journal of Islamic Studies, 2025)
General background: Arabic language learning plays a vital role in Islamic education as it serves as the medium to understand religious sources and express Islamic values. Specific background: In Islamic boarding schools (pesantren), maharah kalam or speaking skill is developed not only through formal instruction but also through habitual and exemplary language practices. Knowledge gap: Previous studies focused mainly on direct teaching or structural approaches to Arabic speaking, while limited attention has been given to the effectiveness of exemplary language models in shaping communicative competence within a linguistic environment. Aims: This study aims to analyze the application of exemplary language practice in maharah kalam learning at the Darul Islam Modern Islamic Boarding School, including its supporting and inhibiting factors. Results: Findings show that consistent language role models, language-area implementation, daily mufrodat, and the supervision system (jasus) foster a living Arabic-speaking environment that strengthens students’ confidence and competence. Novelty: The study highlights the integration of exemplary modeling with disciplinary and motivational systems as a sustainable pedagogical model in Islamic language education. Implications: This approach can serve as a framework for designing Arabic speaking pedagogy grounded in moral exemplarity and linguistic immersion. Highlights: Exemplary practice fosters natural Arabic communication. Leadership and supervision sustain language discipline. Integration of moral and linguistic training enhances learning. Keywords: Exemplary Language, Maharah Kalam, Islamic Education, Language Environment, Arabic Speaking